2021
DOI: 10.14309/ctg.0000000000000300
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Abdominal Adipose Tissue Distribution on Nonalcoholic Fatty Liver Disease and Metabolic Syndrome: A Chinese General Population Study

Abstract: INTRODUCTION: Visceral adipose tissue (VAT) has been found to play a critical role in the development of metabolic syndrome and nonalcoholic fatty liver disease (NAFLD) independent of generalized obesity. METHODS: In this secondary study of prospectively acquired data, 625 participants underwent magnetic resonance spectroscopy and chemical shift fat–water separation MRI (2-point Dixon) of the liver and whole abdomen, respectively, in a 3 Tesla magnet. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…In general, lipodystrophy, obesity, NAFLD, and MS demonstrate disturbances in visceral fat tissue, which together with subcutaneous tissue, form white adipose tissue [188]. Often, the visceral adipose tissue/subcutaneous adipose tissue ratio is increased in NAFLD [189]. Excessive production of FFAs by visceral fat tissue in a pathological situation impairs the PI3K/Akt signaling pathway, increases oxidative stress, and reduces insulin sensitivity [5].…”
Section: Obesitymentioning
confidence: 99%
“…In general, lipodystrophy, obesity, NAFLD, and MS demonstrate disturbances in visceral fat tissue, which together with subcutaneous tissue, form white adipose tissue [188]. Often, the visceral adipose tissue/subcutaneous adipose tissue ratio is increased in NAFLD [189]. Excessive production of FFAs by visceral fat tissue in a pathological situation impairs the PI3K/Akt signaling pathway, increases oxidative stress, and reduces insulin sensitivity [5].…”
Section: Obesitymentioning
confidence: 99%
“…Independent positive association were observed between VAT and NAFLD [21]. And the reverser association between subcutaneous adipose tissue (SAT)and NAFLD has also been reported [22]. It is probably due to retaining adipose tissue in subcutaneous in human obesity could reduce overall and regional-speci c VAT and improve insulin resistance [23].…”
Section: Discussionmentioning
confidence: 92%
“… 20 Chiyanika C suggested that VAT may be a vital driver of NAFLD based on a prospectively acquired data. 16 Another large cohort study indicated that VAT was longitudinally associated with higher risk of incident NAFLD. 15 In terms of severity of NAFLD, we did not get positive result about PrFT, PnFT and NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“… 12–16 The obesity indices in clinical studies included BMI, 12 , 13 waist circumference 14 and visceral obesity. 15 , 16 However, not all obese patients develop NAFLD and, more importantly, NAFLD can occur in nonobese and even lean individuals, especially in Asian populations. Previous study indicated that 40% of global NAFLD patients were non-obese and approximately 20% were lean.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation